Kajian Semantik Kata Qadha dalam Al-Quran: Relevansinya terhadap Koping Religius di Era Modern - Asma Laili Hanifah; Ahmad Nurrohim (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2025)
This study examines the semantic dimensions of the Qur’anic term qadha’ by analyzing its basic meanings, derivations, and contextual functions through syntagmatic and paradigmatic approaches. Using a qualitative descriptive method, the research employs semantic analysis as its primary instrument, drawing data from classical and contemporary lexicons, tafsir works, and concordance-based occurrences of qadha’ in the Qur’an, which appear 56 times in various morphological forms. The syntagmatic analysis explores the relational meaning of qadha’ within its surrounding linguistic structures, revealing its functions in expressing divine decree, legal decisions, fulfillment, completion, and finalization of matters. The paradigmatic analysis compares qadha’ with semantically related terms such as amr, faradha, and atamma, as well as its antonyms like naqadha and ajjala, showing how semantic oppositions and equivalences contribute to the formation of its conceptual range. The findings indicate that qadha’ represents not merely a theological notion but a comprehensive semantic structure that affirms the absoluteness of God’s will in creation, legislation, lifespan, and the resolution of affairs. Furthermore, the study demonstrates that the semantic understanding of qadha’ has significant implications for religious coping, as the belief in divine decree fosters active acceptance, emotional regulation, spiritual connectedness, and resilience when facing psychological and existential pressures. In conclusion, the concept of qadha’ provides a theological foundation that reinforces positive religious coping strategies and remains relevant for addressing the uncertainties and stressors of modern life.